(untitled) - Miller, G. Tyler (George Tyler) (Belmont, CA, 2006)
This book is an interdisciplinary study of how nature works, how people interact with nature and how we can live more sustainably
Keywords: Environmental sciences.,Human ecology.,Environmental protection.,Khoa học môi trường,Sinh thái học nhân văn,Bảo vệ môi trường